2005
DOI: 10.1016/j.tet.2005.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A spectrofluorimetric study of binary fluorophore–cyclodextrin complexes used as chiral selectors

Abstract: Abstract-Six binary complexes between three fluorophores (pyrene, xanthone and anthraquinone) and b-cyclodextrin (b-CD) or heptakis-(6-amino)-(6-deoxy)-b-cyclodextrin (am-b-CD) were tested at two pH values (8.0 and 9.0) as chiral selectors for three a-amino acids chosen as model. The conditional constant (b 2T ) values for ternary complexes (fluorophore-CD-amino acid), determined by means of fluorescence spectroscopy, showed that the binary complexes are suitable receptors for chiral recognition. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As a result, the natural properties of the cyclodextrin amphiphile were greatly affected and vesicles will not be able to form. Since it was reported that anthraquinone can form inclusion complex with β-cyclodextrin, the possible intermolecule inclusion model cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the natural properties of the cyclodextrin amphiphile were greatly affected and vesicles will not be able to form. Since it was reported that anthraquinone can form inclusion complex with β-cyclodextrin, the possible intermolecule inclusion model cannot be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…So the complex stability can be altered by adding a ternary agent. 11,12 As previously reported, 12 a stoichiometric ratio (1/2/2) (fluorophore-cyclodextrin-ternary agent) for ternary complexes studied was determined by means of Job plot analysis. 16 The b 2 value for the ternary complex can be either higher or lower than that for the binary complex.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, we have reported results about the chiral discrimination ability of the binary complexes formed by Py, xanthone and anthraquinone in the presence of both b-cyclodextrin and am-b-CD versus enantiomers of phenylalanine, methionine and histidine. 12 Collected data have shown that the chiral discrimination ability is influenced by the structure of the fluorescent guest and the binary complex symmetry. In this light, both in the presence of the b-CD and am-b-CD, the binary complex formed by Py was the best chiral selector.…”
Section: Introductionmentioning
confidence: 99%